Amplification and bacterium expression of high-molecular-weight glutenin subunit 1Bx14 gene from wheat - JIN Wei-bo; WU Fang-li; GUO Ai-guang (浙江大学学报. 农业与生命科学版, 2007)
HMW-GS 1Bx14 was candidated as a good subunit for dough quality. HMW-GS 1Bx14 coding sequence can be amplified and expressed in vitro for characterizing its function. An improved PCR method was presented for amplification of HMW-GS 1Bx14 which is a fragment of large (about 2.4 kb) and contain GC-rich regions. This experiment adapted following three stratages to optimize PCR system for successful amplification: i) designing a couple of primers with high Tm; ii) Adopting two-temperature PCR; iii) Improving PCR buffer for beneficial long amplicon; adding some organic solvents (DMSO, Lycine) and BSA for resistant to form secondary structure and lengthen in polymerase half-life, respectively. Furthermore, it is very difficulty to express HMW-GS 1Bx14 in E. coli because of the bias of codon usage. The Rosetta (DE3) plysS bacterium was used to conquer the effection of rare codon and express HMW-GS 1Bx14 gene successfully. It will be benefit for further studying on the function of 1Bx14 gene.